Comparative Analysis of Modelling for Piezoelectric Energy Harvesting Solutions - Raj, Jennifer S; Ranganathan, G (Journal of Electrical Engineering and Automation, 2021)
Due to the global energy crisis and environmental degradation, largely as a result of the increased usage of non-renewable energy sources, researchers have become more interested in exploring alternative energy systems, which may harvest energy from natural sources. This research article provides a comparison between various modeling of piezoelectric elements in terms of power generation for energy harvesting solutions. The energy harvesting can be computed and calculated based on piezoelectric materials and modeling for the specific application. The most common type of environmental energy that may be collected and transformed into electricity for several purposes is Piezoelectric transduction, which is more effective, compared to other mechanical energy harvesting techniques, including electrostatic, electromagnetic, and triboelectric transduction, due to their high electromechanical connection factor and piezoelectric coefficients. As a result of this research, scientists are highly interested in piezoelectric energy collection.